2017
DOI: 10.1007/s13593-017-0425-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term negative phosphorus budgets in organic crop rotations deplete plant-available phosphorus from soil

Abstract: In organic farming, phosphorus (P) can be imported in mineral form with rock phosphate, feedstuff for livestock or suitable organic fertilizers. Many organic farmers, however, rely on biological activation of soil P reserves and tolerate P deficits, not knowing when soil reserves will be depleted. We hypothesized that under conditions of a long-term negative P budget in organic farming, the decline in readily available soil P pools would be less pronounced in dairy systems (arable land and grassland) than in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
1
15
0
Order By: Relevance
“…2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 only a few weeks before planting of subsequent crops to better synchronize residue nutrient release and nutrient uptake for the subsequent crop, which was also suggested by Cavigelli and Thien (2003) and Simpson et al (2011). By contrast, in the improved conventional system, fertilizers applied to the field in excess of plant requirements resulted in substantial accumulation of soil P, although our results are consistent with P surpluses that also occurred with mineral fertilizers (Shen et al 2014) and in conventional production with other vegetables (Nesme et al 2011;Yan et al 2013). Based on the soil K system budgets, the improved conventional system had unnecessarily high levels of K fertilization, which was also observed by Korsaeth (2012) for arable conventional systems in a 10-year trial.…”
Section: Gross Nutrient Balancessupporting
confidence: 80%
“…2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 2013 2016 2006 2009 only a few weeks before planting of subsequent crops to better synchronize residue nutrient release and nutrient uptake for the subsequent crop, which was also suggested by Cavigelli and Thien (2003) and Simpson et al (2011). By contrast, in the improved conventional system, fertilizers applied to the field in excess of plant requirements resulted in substantial accumulation of soil P, although our results are consistent with P surpluses that also occurred with mineral fertilizers (Shen et al 2014) and in conventional production with other vegetables (Nesme et al 2011;Yan et al 2013). Based on the soil K system budgets, the improved conventional system had unnecessarily high levels of K fertilization, which was also observed by Korsaeth (2012) for arable conventional systems in a 10-year trial.…”
Section: Gross Nutrient Balancessupporting
confidence: 80%
“…Nayak et al [65] also suggested that phosphatase activities increased by increasing soil organic matter. In another study Ohm et al [66] also found positive relationship between soil carbon and phosphatase activities. Therefore, studying phosphatase activities could be helpful to understand the lability of P under long-term fertilization regulated by soil C:N:P stoichiometry.…”
Section: Discussionmentioning
confidence: 89%
“…The deficiency of Ca and Mg occurs in soils that are intensively cultivated. In same way, P balances the cropping systems but when more P is removed with the products than recycled via external inputs (21), it threatens the long-term sustainability of farming systems (19,21). While soil organic matter (SOM) and soil macronutrients are crucial elements of soil-plant ecosystems (22), the soil pH diagnoses soil nutrient deficiency or toxicity problem (23,24).…”
Section: Introductionmentioning
confidence: 99%